ADVANCING PHYSICS AND SCIENCE EDUCATION THROUGH INNOVATIVE TECHNOLOGIES AND PEDAGOGICAL STRATEGIES - Nassiri, Siti Hidayana; Khamis, Noorzana; Bunyamin, Muhammad Abd Hadi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Physics education continues to face persistent challenges, including abstract content, entrenched misconceptions, and declining student engagement. Recent innovations in technology, pedagogy, assessment, and curriculum offer opportunities to address these issues, but their impact depends on coherent integration rather than isolated adoption. Drawing on 52 articles published between 2010 and 2025, this review synthesizes developments across five thematic domains: technological innovations, pedagogical strategies, teacher professional development, assessment practices, and curriculum integration. The findings highlight that tools such as virtual laboratories, artificial intelligence, and AR/VR environments can expand inquiry-based learning, yet they require strong pedagogical grounding to move beyond novelty. Active, inquiry-oriented, and collaborative strategies enhance conceptual understanding but remain resource-intensive. Teacher professional development emerges as the linchpin of sustainable reform, underscoring the need for iterative, reflective, and practice-oriented models that strengthen pedagogical content knowledge and professional identity. Assessment practices must evolve from reliance on concept inventories toward authentic, technology-enhanced approaches that capture higher-order competencies. Curriculum reform, through interdisciplinary STEM links and sustainability themes, provides systemic opportunities but also raises concerns regarding equity and scalability. This review concludes that meaningful transformation in physics education requires coherence across technologies, pedagogies, assessments, and curricula.